2022
DOI: 10.1111/head.14320
|View full text |Cite
|
Sign up to set email alerts
|

Normal glymphatic system function in patients with migraine: A pilot study

Abstract: Objective No studies have evaluated the glymphatic system function in patients with migraine. In this pilot study, we evaluated and compared the alterations in the glymphatic system function in patients with migraine with healthy controls using a diffusion tensor imaging (DTI) analysis along the perivascular space (DTI‐ALPS) method. We also investigated the differences in the glymphatic system function table between patients with migraine with and without aura using the ALPS method. Methods This field study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
3
26
1
Order By: Relevance
“…Although the exact pathogenesis and pathophysiology of NDPH are not fully understood, headache attacks in patients with NDPH may be related to chronic neurological inflammation, cytokine production, and persistent glial activation in response to the triggering events mentioned above 16 . Consistent with our findings, a recent study using the ALPS index revealed normal glymphatic function in patients with migraine 34 . Although NDPH and migraine are distinct types of headache, there is no evidence that either type has an underlying association with neurodegenerative disease 37,38 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the exact pathogenesis and pathophysiology of NDPH are not fully understood, headache attacks in patients with NDPH may be related to chronic neurological inflammation, cytokine production, and persistent glial activation in response to the triggering events mentioned above 16 . Consistent with our findings, a recent study using the ALPS index revealed normal glymphatic function in patients with migraine 34 . Although NDPH and migraine are distinct types of headache, there is no evidence that either type has an underlying association with neurodegenerative disease 37,38 .…”
Section: Discussionsupporting
confidence: 90%
“…16 Consistent with our findings, a recent study using the ALPS index revealed normal glymphatic function in patients with migraine. 34 Although NDPH and migraine are distinct types of headache, there is no evidence that either type has an underlying association with neurodegenerative disease. 37,38 This difference in the nature of the disorders explains that the glymphatic system may not be directly involved in the pathophysiology of headaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourthly, impaired glymphatic clearance function is related to WMHs in patients with cerebral small vessel disease ( Xu et al, 2022 , Zhang et al, 2021 ). However, the current evidence does not find glymphatic dysfunction in migraineurs compared to healthy controls ( Lee et al, 2022 ). Finally, blood–brain barrier damage is a fundamental disease mechanism in WMHs ( Wardlaw et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 66%